Strategies for recruiting a sample of adults with type 2 diabetes from primary care clinics in rural Appalachia: Incorporating cultural competence - Roger Carpenter, PhD, RN; Laurie A. Theeke, PhD, FNP-BC (Elsevier, 2018)
Background: Recruiting research participants from primary care in rural Appalachia is a major challenge and can be influenced by cultural characteristics, making it critically important to incorporate strategies of cultural competence in the overall design of clinical research. Objectives: The purpose of this paper is to describe culturally competent strategies used for recruitment and data collection with a sample of adults with type 2 diabetes from primary care settings in Appalachia. Design: The Purnell model of cultural competence and relevant literature served as a framework for study design. Four overarching approaches informed the organization of recruitment strategies and development of the data collection plan. Procedures: The approaches included selection of research sites, establishing collaborations, sustaining collaborative relationships, and enhancing understanding of benefits of participation. Four recruitment sites were selected based on potential to enhance diversification of participants; multiple steps were included in each of the three remaining approaches to build relationships and gain participation. A study log was maintained to provide evaluation data. Results: Recruitment took 14 months and a sample of 102 subjects provided consent with 101 participants providing complete data. Demographics were representative of the region except that African American participation was higher (6.9%) compared to current north central Appalachia (3%). Over 72% of participants indicated they would be interested in participating in future studies. Conclusions: These findings emphasize the importance of employing strategies for cultural competence in study design. Use of concepts from the Purnell model led to enhanced representativeness and potential for subsequent generalizability. Keywords: Adult, Appalachian region, Cultural characteristics, Cultural competency, Diabetes mellitus, Type 2, Primary health care, Recruitment